Effect of Persistent Fibroma Virus Infection on Susceptibility of Cells to Other Viruses - Padgett, Billie L. (1970)
Shope fibroma virus establishes a persistent cytoplasmic infection in primary (RK) and serially cultivated (DRK(3)) rabbit kidney cells which is accompanied by a morphological alteration of the cells. The response of such cells to superinfection by other viruses was compared with that of control cells by determining plaque production and virus yield of superinfecting viruses. It was found that the growth of other poxviruses, myxoma and vaccinia, was greatly inhibited in the fibroma virus-infected cells, but that of pseudorabies and herpes simplex viruses, which are unrelated deoxyribonucleic acid viruses, was virtually unaffected. The ribonucleic acid (RNA) viruses, poliovirus 1 and coxsackievirus B1, did not produce plaques on either RK or fibroma virus-infected (F-RK) monolayers. However, the growth of several other RNA viruses, vesicular stomatitis virus, encephalomyocarditis virus, Sindbis virus, and Newcastle disease virus, was enhanced in F-RK cells. None of these latter RNA viruses produced any infectious progeny in DRK(3) cells, but they all plaqued on and produced good yields in DRK(3) cells persistently infected with fibroma virus. This phenomenon is termed facilitation. Facilitation results from the infection of DRK(3) cells by fibroma virus. Neither interference nor facilitation were due to changes in the adsorption or eclipse of the superinfecting virus.